Implementación de tecnologías de información y administración del conocimiento en empresas consultoras (Estudios) - Arévalo Avecillas, Danny (2017)
The article analyzes consulting firms in Guayaquil, which use as a means of innovation, the implementation of information technologies in their daily activities. The methodology is qualitative; and the tool used an interview. The contribution of the research is the construction of a cognitive map of information technologies for companies that seek to improve their productivity through the implementation of technology.